IOT BASED SMART REMOTE PATIENT MONITORING SYSTEM - Pawan Kumar Choudhary,; Jayati Vasavada, (International Journal of Innovations in Engineering Research and Technology, 2021)
Many lives are lost every day in India because patients are not treated in a timely and proper manner. In addition, in clinics and hospitals, parameter values are not accurately calculated in real time. It can be difficult for hospital staff to keep track of patients' conditions on a regular basis. In addition, ICU patients cannot be monitored continuously. Our framework is useful in dealing with these types of circumstances. Our device is intended for use in hospitals as well as in home to measure a variety of parameters such as temperature, ECG, and heart rate and humidity. All these operations are performed with the help of a microcontroller Arduino Uno R3, also the data are stored in a host server namely ‘Thingspeak’, with the help of Wi-Fi module, so the doctors or the consent person keep an eye on the patient continuously.